Synthesis of novel 2-substituted benzimidazole derivatives as potential anti microbial agents - Selvam, T. Panneer; Radhika, P. P.; Janagaraj, S.; Kumar, A. Siva (Research in Biotechnology, 2011)
In the present study, a novel series of 2-substituted benzimidazole derivatives were synthesized and characterized by means of IR, 1H-NMR, 13C- NMR, mass spectral and elemental analysis. The compounds were screened for antibacterial (Staphylococcus aureus ATCC9144, Staphylococcus epidermidis ATCC 155, klebsiella pneumoniae ATCC 29665 and Esherichia coli ATCC 25922) and antifungal (Candida albicans ATCC 2091 and Aspergillus niger ATCC 9029) activities. The Minimum Inhibitory Concentrations was determined by agar streak dilution method. 1-(4-(1H-benzo[d]imidazol-2-yl)phenyl)-3-chloro-4-(4-nitro phenyl)azetidin-2-one (3a) was found to exhibit the most potent in vitro antimicrobial activity with MIC of 15, 17, 19, 9, 11 and 15 μg/mL against E.coli, K.pneumoniae, S.aureus, S.epidermidis, C.albicans and A.niger respectively. All the other compounds exhibited moderate activity against the bacterial and fungal organism tested.